A case study on rural senior citizens’ reading materials / Hashim Ismail, Wan Ab Kadir Wan Dollah, and Mohd Fazli Abd. Malek - Ismail, Hashim; Wan Dollah, Wan Ab Kadir; Abd. Malek, Mohd Fazli (Universiti Teknologi MARA, 2020)
Senior citizens play an important role in the development of future societies. It is anticipated that the elderly population in Malaysia will increase by 15 percent to 5.6 million by 2030 due to the progressive advancement in healthcare facilities over the last 50 years, hence leading to longer life expectancy. In line with the development of knowledge networks, literary materials have become more diverse for senior citizens to choose from in order to improve their quality of life. This article aims to identify and analyse the different types of literature reading material and its contents, as well as to propose other literary materials especially for the necessity of the rural libraries in Kelantan. This study uses a quantitative approach: a field study using a questionnaire distributed to 300 senior citizens in Kelantan and analysed using the Statistical Package for Social Sciences (SPSS). Findings showed that the senior citizens chose religious literature as their preferred reading materials. In conclusion, the choice of reading materials by senior citizens in rural areas should be considered by the library management and publishing companies to ensure that they can gain better benefits